Development of the Science Knowledge Application on Temperature, Heat, and Expansion to Improve Student Learning Outcomes - Mokoginta, Chindy Dahlia; Mursalin, Mursalin; Payu, Citron S.; Abdjul, Tirtawaty; Ntobuo, Nova Elysia; Uloli, Ritin (Jurnal Pijar Mipa, 2025)
Sains Knowledge is an application developed to support student learning. This study aims to examine the validity, practicality, and effectiveness of the Sains Knowledge application in improving student learning outcomes on the topics of temperature, heat, and expansion. The research employed a One-Group pretest–posttest design, with data analyzed using the N-gain test. The study was conducted with seventh-grade students (Class VII-A) at SMP Negeri 11, Gorontalo City, and employed a Research and Development (R&D) approach based on the 4D model, comprising the stages of define, design, development, and dissemination. The findings show that Sains Knowledge met the eligibility criteria as a learning medium, with an average validation score of 94%. The practicality instruments indicated a 92% implementation rate, while student responses fell into the “very good” category at 80% and the “good” category at 20%. In terms of effectiveness, student activity reached 86%, and learning outcomes improved from an average score of 48 (pretest) to 90 (posttest), with an average N-gain of 0.81 in the “high” category. These results demonstrate that the Sains Knowledge application is valid, practical, and effective in enhancing student learning outcomes, with broader implications for improving digital learning media in secondary education.